Living with depression and diabetes: A qualitative study in Bangladesh and Pakistan. - Hannah Maria Jennings; Ashraful Anas; Sara Asmat; Anum Naz; Saima Afaq; Naveed Ahmed; Faiza Aslam; Gerardo Zavala Gomez; Najma Siddiqi; David Ekers (Public Library of Science (PLoS), 2024)
Diabetes and depression are both serious health conditions. While their relationship is bidirectional and each condition adversely affects outcomes for the other, they are treated separately. In low and middle income countries, such as Bangladesh and Pakistan, health systems are already stretched and the integration of diabetes and depression care is rarely a priority. Within this context through interviews with patients, healthcare workers and policy makers the study explored: lived experiences of people living with depression and diabetes, current practice in mental health and diabetes care and barriers and perspectives on integrating a brief psychological therapy into diabetes care. The findings of the study included: differing patient and practitioner understandings of distress/depression, high levels of stigma for mental health and a lack of awareness and training on treating depression. While it was apparent there is a need for more holistic care and the concept of a brief psychological intervention appeared acceptable to participants, many logistical barriers to integrating a mental health intervention into diabetes care were identified. The study highlights the importance of context and of recognising drivers and understandings of distress when planning for more integrated mental and physical health services, and specifically when adapting and implementing a new intervention into existing services.